2012
DOI: 10.3758/s13421-012-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotion and encoding strategy on associative memory

Abstract: Research has demonstrated that when discrete pieces of information are integrated together at encodingimagining two items together as a single entity, for examplethere is a mnemonic benefit for their relationship. A separate body of literature has indicated that the presence of emotional information can have an impact on the binding of associated neutral details, in some cases facilitating associative binding (MacKay et al. Memory and Cognition 32:474-488, 2004; Mather, Perspectives on Psychological Science 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 32 publications
9
63
1
Order By: Relevance
“…The findings from Murray and Kensinger (2012) support the prioritized binding theory discussed earlier, in part, but also revealed a time-dependent effect of the benefit of emotional salience. They found that when participants were asked to integrate two verbal paired associates together as one representation, given 2 seconds to encode, there was a significant mnemonic benefit for emotional-neutral pairs over neutral-neutral pairs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The findings from Murray and Kensinger (2012) support the prioritized binding theory discussed earlier, in part, but also revealed a time-dependent effect of the benefit of emotional salience. They found that when participants were asked to integrate two verbal paired associates together as one representation, given 2 seconds to encode, there was a significant mnemonic benefit for emotional-neutral pairs over neutral-neutral pairs.…”
Section: Discussionsupporting
confidence: 76%
“…Alternatively, and perhaps more likely, because of the salient nature of the negative objects, the emotional face-object pairs, although encoded into an integrated memory trace to a similar degree as the neutral face-object pairs, were perhaps encoded quicker yet shallower than the neutral pairs, similar to Murray and Kensinger (2012). The findings from Murray and Kensinger (2012) support the prioritized binding theory discussed earlier, in part, but also revealed a time-dependent effect of the benefit of emotional salience.…”
Section: Discussionsupporting
confidence: 75%
“…One reason for this discrepancy could be related to item-context binding processes (Mackay et al, 2004;Mather, 2007), which were facilitated methodologically in the present study. It has been observed that contextual memory increases when neutral items are well integrated with other items or contexts (Murray & Kensinger, 2012, especially when the latter are arousing (Guillet & Arndt, 2009;Pierce & Kensinger, 2011). Compared to previous studies (e.g., Jaeger & Rugg, 2012), we facilitated item-context pairing by integrating the object into the scene.…”
Section: Discussionmentioning
confidence: 82%
“…Sometimes, through the process of integration, we experience and remember these items as parts of a whole rather than as separate entities. Recent research with younger adults has demonstrated that successfully integrating two non-emotional items at encoding, instead of imagining them separately, produces a disproportionately larger associative memory benefit than integrating an emotional and a non-emotional item (Murray & Kensinger, 2012). In the first study to examine whether age and emotion interact to influence integration, we use two measures of integrative success – the ability to successfully retrieve integrations, measured through associative cued recall, and the ability to successfully generate integrated representations at encoding, measured through self report.…”
mentioning
confidence: 99%
“…When we previously examined the effect of instructed integration on younger adults’ ability to form integrated images and to remember the pairs, we (Murray & Kensinger, 2012) demonstrated that college-age participants were able to integrate an emotional and a neutral item at encoding when instructed to do so. Even when under time pressure, they reported high success in creating a mental image that integrated the two concepts, suggesting that the attentional pull of the emotional item was insufficient to disrupt the process of integration when such integration was task-relevant.…”
mentioning
confidence: 99%